2017
DOI: 10.7448/ias.20.1.21930
|View full text |Cite
|
Sign up to set email alerts
|

Multicentre analysis of second‐line antiretroviral treatment in HIV‐infected children: adolescents at high risk of failure

Abstract: Introduction: The number of HIV-infected children and adolescents requiring second-line antiretroviral treatment (ART) is increasing in low- and middle-income countries (LMIC). However, the effectiveness of paediatric second-line ART and potential risk factors for virologic failure are poorly characterized. We performed an aggregate analysis of second-line ART outcomes for children and assessed the need for paediatric third-line ART. Methods: We performed a multicentre analysis by systematically reviewing the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

10
25
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 34 publications
10
25
1
Order By: Relevance
“…This confirms the event of early ART failure among children and the need for timeous viral load monitoring, as previously reported in the several settings of the same country [14,22,34]. This early ART failure associated with high rate of HIVDR should be addressed critically, as this may indicate a rapid selection of DRMs pre-existing as minority variants upon pharmacological pressure [34,36,37], and/or compliance challenges as children grow towards adolescence [15,39].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This confirms the event of early ART failure among children and the need for timeous viral load monitoring, as previously reported in the several settings of the same country [14,22,34]. This early ART failure associated with high rate of HIVDR should be addressed critically, as this may indicate a rapid selection of DRMs pre-existing as minority variants upon pharmacological pressure [34,36,37], and/or compliance challenges as children grow towards adolescence [15,39].…”
Section: Discussionsupporting
confidence: 84%
“…The high burden of ADR among children failing the first-and second-line regimens reveal almost complete inefficacy of NNRTIs and NRTIs, which are low genetic barrier drugs, contributing to early selection of DRMs among children, especially in the frame of poor compliance to ART regularly reported among children and adolescents [15,34,39]. Interestingly, dual-class of resistance to NNRTI and NRTI remains very high (>80%) among children failing first-and second-line ART, with very low rate resistance to PI/r.…”
Section: Discussionmentioning
confidence: 99%
“…We found that older age significantly increased the risk of treatment failure in our cohort. Since adolescence is a vulnerable period, several challenges they experience may result in adherence problems and eventually treatment failure, especially for those with perinatally acquired HIV infection who started cART at very young ages . Additionally, advanced HIV disease before cART initiation was associated with treatment failure, which has been observed in other studies .…”
Section: Discussionsupporting
confidence: 60%
“…Additional barriers to VLS in adolescents include drug toxicity and intolerance, psychological problems (depression, anxiety, and trauma) and social barriers, including stigma, have been linked to poor treatment adherence in adolescents and young adults. [57][58][59][60] Important limitations of the study are that genotyping results after first-line ART failure were not always available in realtime to health care providers for the optimization of ART before switching to second-line regimens. In addition, limited adherence and ATV/r as second-line ART may have reduced the rate of VS 50 .…”
Section: Discussionmentioning
confidence: 99%